Systemic neoadjuvant chemotherapy for Group B intraocular retinoblastoma (ARET0331): A report from the Children's Oncology Group. Issue 7 (26th December 2016) - Friedman, Debra L.; Krailo, Mark; Villaluna, Doojduen; Gombos, Dan; Langholz, Bryan; Jubran, Rima; Shields, Carol; Murphree, Linn; O'Brien, Joan; Kessel, Sandra; Rodriguez‐Galindo, Carlos; Chintagumpala, Murali; et al.
Abstract: Purpose: To evaluate a chemoreduction regimen using systemic vincristine and carboplatin (VC) and local ophthalmic therapies to avoid external‐beam radiotherapy (EBRT) or enucleation in patients with Group B intraocular retinoblastoma. Patients and methods: Twenty‐one patients (25 eyes) were treated with six cycles of VC, accompanied by local ophthalmic therapies after cycle 1. The primary study objective was to determine the 2‐year event‐free survival (EFS) where an event was defined as the use of systemic chemotherapy in addition to vincristine or carboplatin, EBRT, and/or enucleation. Results: All patients had tumor regression after the first cycle of VC and only two patients had progression during therapy. There were seven treatment failures within 2 years of study enrollment, resulting in 2‐year EFS of 65% and early study closure in accordance with the statistical design. The 2‐year cumulative incidence of enucleation was 15%; for external beam radiation therapy, it was 10%; and for chemotherapy to control progressive disease, it was 10%. All patients sustaining a treatment failure were salvaged with additional therapy. Conclusions: For the majority of patients with Group B intraocular retinoblastoma, chemoreduction with VC, without etoposide, in conjunction with local therapy provides excellent opportunity for ocular salvage. Local therapy given with every chemotherapy cycle and incorporation of etoposide may provide improved ocular salvage rates. Central review of group at diagnosis is critical in assigning appropriate therapies.